Integration Of Servperf Ipa And Qfd In Improving The Quality Of Construction Engineering Consultant Services Based On The Client's Perspective - Muhammad Zulfiqar Daffa; Haryo Dwito Armono (Publikasi Indonesia, 2025)
Business-to-business (B2B) services in the consulting industry form the foundation of interactions between clients and consultants. The quality of services provided by construction engineering consultants is a primary concern for clients, particularly in light of recurring complaints stemming from service quality that fails to meet expectations. In response to these issues, this study was conducted to enhance the quality of services offered by construction engineering consultants, with the aim of meeting client expectations and improving overall satisfaction. This research employs the SERVPERF (Service Performance), Importance–Performance Analysis (IPA), and Quality Function Deployment (QFD) methods to formulate technical recommendations for service quality improvement. The SERVPERF method is used to evaluate service performance based on client perceptions, the IPA method is applied to identify the Voice of the Customer, and the QFD method serves to translate client needs and expectations into technical specifications that can be implemented by consultants. The study identified and assessed 20 service quality attributes across six dimensions—Tangibles, Assurance, Reliability, Responsiveness, Empathy, and Flexibility—highlighting the alignment between performance satisfaction and client priorities. Among these, 10 attributes were found to be most significant and representative of the Voice of the Customer. The study proposes three priority recommendations improve service quality: (1) implementation of project KPI evaluation dashboards, comprehensive progress reporting, daily client service updates; (2) automation of numerical and qualitative testing for technical documents, aligned with classification standards, tagging systems, standard operating procedures, templates technical guidelines; (3) deployment of a notification system to inform stakeholders of project progress and status changes.